N2-to-NH3 conversion by excess electrons trapped in point vacancies on 5f-element dioxide surfaces - Wang, Gaoxue; Batista, Enrique R.; Yang, Ping (Frontiers in Chemistry, 2023)
Ammonia (NH3) is one of the basic chemicals in artificial fertilizers and a promising carbon-free energy storage carrier. Its industrial synthesis is typically realized via the Haber-Bosch process using traditional iron-based catalysts. Developing advanced catalysts that can reduce the N2 activation barrier and make the NH3 synthesis more efficient is a long-term goal in the field. Most heterogeneous catalysts for N2-to-NH3 conversion are multicomponent systems with singly dispersed metal clusters on supporting materials to activate N2 and H2 molecules. Herein we report single-component heterogeneous catalysts based on 5f actinide dioxide surfaces (ThO2 and UO2) with oxygen vacancy for N2-to-NH3 conversion. The reaction cycle we propose is enabled by a dual-site mechanism, where N2 and H2 can be activated at different vacancy sites on the same surface, and NH3 is subsequently formed via the associative pathways by H- migration on the surface. The oxygen vacancies will recover to initial states after the release of two molecules of NH3, making it possible for the catalytic cycle to continue. Our work demonstrates the catalytic activity of oxygen vacancies on 5f actinide dioxide surfaces for N2 activation, which may inspire the search for highly-efficient single-component catalysts that are easy to be synthesized and controlled for NH3 conversion.